Ethical Standards and Accountability of Election Organizers in Handling Code of Ethics Violations in Makassar City - Pasalli, Roy Pole; Ibrahim, Muhammad Akman; Lambali, Suryadi; Bachtiar, Naylawati (Departemen Ilmu Administrasi FISIP UNHAS, 2023)
The election organizing organization is one of the objects of public administration studies with problems related to ethics and accountability. If the ethical discourse in organizations revolves around the relationship between individuals, values, and the environment, then leadership can be seen as distilling those factors in an individual. One of the district/city-level election organizers, namely the Makassar City KPU, has a significant number of cases of ethical violations by ad hoc bodies. This violation indeed cannot be separated from the leadership of the Makassar City KPU in handling it. This research uses qualitative methods with a case study design. Data collection techniques are carried out by in-depth interviews and document studies. Data was analyzed using the Miles and Huberman model of data reduction, data presentation, and conclusions. The results showed that the Makassar City KPU is still partial in showing the characteristics of ethical leadership by Trevino et al. (2003) in the aspects of setting ethical standards and accountability. This is because the Makassar City KPU generally has moral standards and rules for handling ethical violations contained in PKPU No. 8 of 2022. However, the Makassar City KPU still needs to comply with these rules. This is shown from several cases of ethical violations, where the Makassar City KPU was again reported to the DKPP based on procedural non-compliance with KPU Decree No. 337/HK.06.2-Kpt/01/KPU/VII/2020, which contains related to handling violations of the Code of ethics by ad hoc bodies. In addition, implementing ethical standards and managing ethical violations must also be based on local culture, namely siri' culture in the people of Makassar. However, this has not been practiced well by the Makassar City KPU, so it is prone to causing miscommunication and offense between parties.